2022
DOI: 10.3390/ijerph19052603
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Anxiety among Women during the COVID-19 Pandemic—A Cross-Sectional Study

Abstract: Introduction: The COVID-19 pandemic has changed the way prenatal education and obstetric care are provided. Pandemic-related anxiety, restrictions, limitations in perinatal care, and the inability to be accompanied by a loved one can have negative psychological consequences for future parents and their child. The aim of this study was to analyze the determinants and assess the anxiety of pregnant women in individual trimesters, as well as to learn about the sources of support and medical personnel proceeding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…This is in line with the results of the study conducted by King et al, which revealed that pregnant women during the pandemic were twice as likely to suffer from depression [ 35 ]. Similarly to anxiety, some factors might increase the risk of depression in pregnancy; these are believed to be the physical and mental condition of the mother, earlier maternal experiences, relationship and epidemiological circumstances [ 36 ], lower education level, unemployment, reduction in perception of general support, and financial problems [ 14 ]. Interestingly, recent studies, including our own, have shown that the COVID-19 pandemic may increase the prevalence of perinatal and postpartum depression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the results of the study conducted by King et al, which revealed that pregnant women during the pandemic were twice as likely to suffer from depression [ 35 ]. Similarly to anxiety, some factors might increase the risk of depression in pregnancy; these are believed to be the physical and mental condition of the mother, earlier maternal experiences, relationship and epidemiological circumstances [ 36 ], lower education level, unemployment, reduction in perception of general support, and financial problems [ 14 ]. Interestingly, recent studies, including our own, have shown that the COVID-19 pandemic may increase the prevalence of perinatal and postpartum depression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As studies have shown, there is a significant correlation between the amount of perceived support from the partner and depression or anxiety level, especially among pregnant women. According to the research by Iwanowicz-Palus et al, support from loved ones was significant in achieving a good psychological condition and decreasing anxiety during childbirth in the COVID-19 epidemiological situation [ 36 ]. Furthermore, in their study, Zhang et al emphasized the link between stress derived from lifestyle restrictions or insufficient emotional and instrumental support during pregnancy, and the hypersecretion of cortisol, which is considered to be a biologic risk factor for depression [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced, perinatal mental health is a leading public health issue associated with negative effects on both maternal and child health outcomes and significant economic cost [23] , [29] . This is without the further risk of pandemic-related anxiety and social isolation that can lead to ongoing negative psychological outcomes [49] . Thus, in promoting mental health and wellbeing during a time where reconfiguration of service delivery was required, we sought to assess a hybrid model of pregnancy care, i.e., telehealth and fewer in-person health assessments, coupled with concurrent small group interdisciplinary psychoeducation delivered via video conferencing that extended into the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature on the subject is examined, it is seen that the studies are generally related to pregnancy (Bostan & Kabukcuoglu, 2022;Castillo et al, 2022;Shimpuku et al, 2022), prenatal care (Das et al, 2022;Iwanowicz-Palus et al, 2022;Zbiri et al, 2021), depression (Shimpuku et al, 2022;Wu & Wang, 2022;Zhang et al, 2021), social support (McCormack et al, 2021Rayburn & Coatsworth, 2021), self-sufficiency (Bostan & Kabukcuoglu, 2022;Diotaiuti et al, 2022;Eidouzaei et al, 2022), fear of childbirth (Buran & Aksu, 2022;Eidouzaei et al, 2022;Gökçe İşbir et al, 2022), anxiety (Diotaiuti et al, 2022;Gargari et al, 2021;Iwanowicz-Palus et al, 2022), obesity (Hurst et al, 2021;Ortiz-Felix et al, 2021), breastfeeding (Bookhart et al, 2021;Oggero & Wardell, 2022;Taha et al, 2022), parenting (Abbass-Dick et al, 2017, postpartum care (Gagnon & Sandall, 2007;Hunter et al, 2009), quality improvement (Hurst et al, 2021;Louis-Jacques et al, 2020;Takako, 2020).…”
Section: Introductionmentioning
confidence: 99%